Factors associated with parents' decision to bring their children to the Ukp service of Muara Kulam Health Center, North Musi Rawas Regency in 2023 - Prasetio, Bangun; Samidah, Ida; RS, Danur Azissah (Universitas Dehasen Bengkulu, 2024)
Individual Health Efforts (UKP) or often called curative services, the target is individuals and or households. The orientation is the healing and rehabilitation of someone who falls ill. UPT Puskesmas Muara Kulam is an inpatient health center, which in its implementation implements programs both Public Health Service Efforts (UKM) and Individual Health Efforts (UKP). The utilization of basic health services by the community in 2020 was 45.8% of the 12,021 population.The purpose of this study was to determine the factors associated with the decision of parents to bring their children to the UKP service of the Muara Kulam Puskesmas, North Musi Rawas Regency in 2023.This type of research is analytical observational with a cross sectional design. The sample size of this study was 62 respondents selected by putposive sampling technique. The instrument used was a questionnaire. Data were analyzed using the chi-square test. The results showed that there was no relationship between age, education, employment, ownership of health insurance, availability of health workers and accessibility with the decision of parents to bring their children to the UKP Puskesmas Muara Kulam Mutara District. While for the perception of pain there is a significant relationship with a value of p=0.002. This study should be used as information and reference material to examine how to improve the utilization of health services at the puskesmas.